Maintaining Momentum Toward Graduation: OER and the Course Throughput Rate - Hilton III, John; Fischer, Lane; Wiley, David; Williams, Linda (International Review of Research in Open and Distributed Learning, 2016)
Open Educational Resources (OER) have the potential to replace traditional textbooks in higher education. Previous studies indicate that use of OER results in high student and faculty satisfaction, lower costs, and similar or better educational outcomes. In this case study, we compared students using traditional textbooks with those using OER at Tidewater Community College to compare their performance on what we call course throughput rates, which is an aggregate of three variables – drop rates, withdrawal rates, and C or better rates. Two self-selecting cohorts were compared over four semesters, with statistically significant results. The study found that, subject to the limitations discussed, students who use OER perform significantly better on the course throughput rate than their peers who use traditional textbooks, in both face-to-face and online courses that use OER. This suggests that OER are a promising avenue for reducing the costs of higher education while increasing academic success.